(untitled) (Dristikon: A Multidisciplinary Journal, 2020)
The paper aims to examine the relationship between interest rate spread (IRS) and profitability and the impact of IRS on profitability of commercial banks in Nepal. Secondary data have been collected from the annual reports of Nepal investment bank ltd. from fiscal year 2066/67 to 2075/76. A regression technique has been used considering statistical package Minitab 16 version to analyze the data. The study reveals the positive impact of IRS upon the profitability of Nepal investment bank ltd. This study provides sufficient evidences to Nepalese commercial banks about the impact of their IRS on their profitability. The result of this study motivates to Nepalese commercial banks to understand the importance of IRS to raise profitability. Based on the findings, the study is useful to Nepalese commercial banks for making balance between deposit rate and lending rate and maintaining optimum level of interest rate spread to attract both depositors and debtors. This study is also useful to new researchers as a reference for conducting study on similar topic.